Volitional imagining and religious dramatizing - Smith, Steven G. (International journal of philosophy and theology, 2024)
Prompted and resolved by acts of volitional imagining, dramatizing figures a situation in which actors share in having something important at stake such that imminently some of their actions will be momentous (making great differences) and fateful (defining of lives). Religious dramatizing does this very ambitiously. In amplifying the stakes of action there is a danger of being inappropriately dramatic, as in Don Quixote’s fantasies or Chicken Little’s ‘The sky is falling!’ But dramatization can be validated by successfully enacting the dramatic heightening of a situation, by conventionally instituting heights of importance, and by having convincing experiences of situations as dramatic. Kant worries about an inappropriately romantic dramatizing of the moral life; Lucretius warns that religious visionaries will make people crazy with fear of divine retribution. The issue is taken seriously within religious dramatizing. For example, apocalypticism seems to entail an irresponsible termination of care for continuing life. Correctives are offered by Hans Urs von Balthasar’s theory of ‘theo-drama’ and (Francis’s, 2015) encyclical ‘On Care for Our Common Home’. These examples show how the modulation of dramatizing is no less a religious concern than the dramatic heightening of human life.